How the protease thrombin talks to cells - Coughlin, Shaun R. (The National Academy of Sciences, 1999)
How does a protease act like a hormone to regulate cellular functions? The coagulation protease thrombin (EC 3.4.21.5) activates platelets and regulates the behavior of other cells by means of G protein-coupled protease-activated receptors (PARs). PAR1 is activated when thrombin binds to and cleaves its amino-terminal exodomain to unmask a new receptor amino terminus. This new amino terminus then serves as a tethered peptide ligand, binding intramolecularly to the body of the receptor to effect transmembrane signaling. The irreversibility of PAR1’s proteolytic activation mechanism stands in contrast to the reversible ligand binding that activates classical G protein-coupled receptors and compels special mechanisms for desensitization and resensitization. In endothelial cells and fibroblasts, activated PAR1 rapidly internalizes and then sorts to lysosomes rather than recycling to the plasma membrane as do classical G protein-coupled receptors. This trafficking behavior is critical for termination of thrombin signaling. An intracellular pool of thrombin receptors refreshes the cell surface with naïve receptors, thereby maintaining thrombin responsiveness. Thus cells have evolved a trafficking solution to the signaling problem presented by PARs. Four PARs have now been identified. PAR1, PAR3, and PAR4 can all be activated by thrombin. PAR2 is activated by trypsin and by trypsin-like proteases but not by thrombin. Recent studies with knockout mice, receptor-activating peptides, and blocking antibodies are beginning to define the role of these receptors in vivo.